Strain Rate Effect on the Strength of Frozen Silt. - Haynes,F. D.; Karalius,J. A.; Kalafut,J. (1975)
Uniaxial compression and tension tests were conducted on frozen Fairbanks silt at a temperature of -10 C. A relatively stiff testing machine was operated at a constant displacement rate for each test. The tests showed that compressive strength is very sensitive to strain rate and the tensile strength is relatively insensitive to it. The compressive strength increased ten times over a srain rate range of .00012/S to 2.9/s. As was found in other investigations, tangent moduli increased slightly with greater strain rates. The specific eney increased at higher strain rates for compression tests and decreased slightly for tension tests. For increased strain rates, uniaxial compression strength showed no tendency to plateua; nor did the specific energy a minimum during uniaxial tensile testing. (Author)